2010
DOI: 10.3109/14767058.2010.482622
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and risk factors of funisitis and histologic chorioamnionitis in pregnant women at term who delivered after the spontaneous onset of labor

Abstract: Objective To examine the frequency and risk factors of funisitis and histologic chorioamnionitis in the placentas of term pregnant women who delivered after the spontaneous onset of labor. Methods The frequency of funisitis and histologic chorioamnionitis was examined in consecutive pregnant women at term with singleton pregnancies who delivered after the spontaneous onset of labor. Nonparametric statistics were used for data analysis. Results 1) The frequency of funisitis and histologic chorioamnionitis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…In term gestations, acute histologic chorioamnionitis is more common in patients who undergo spontaneous labor than in those who deliver by cesarean section without labor [160, 235]. Moreover, the more advanced the cervical dilatation is at the time of a cesarean delivery, the greater the risk of acute histologic chorioamnionitis and microbial invasion of the amniotic cavity [236, 237]. Other studies have documented that acute histologic chorioamnionitis is associated with the presence of bacteria in the chorioamniotic space [150, 151, 238], although the strength of this association varies between term and preterm gestations [172, 173].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In term gestations, acute histologic chorioamnionitis is more common in patients who undergo spontaneous labor than in those who deliver by cesarean section without labor [160, 235]. Moreover, the more advanced the cervical dilatation is at the time of a cesarean delivery, the greater the risk of acute histologic chorioamnionitis and microbial invasion of the amniotic cavity [236, 237]. Other studies have documented that acute histologic chorioamnionitis is associated with the presence of bacteria in the chorioamniotic space [150, 151, 238], although the strength of this association varies between term and preterm gestations [172, 173].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have documented that acute histologic chorioamnionitis is associated with the presence of bacteria in the chorioamniotic space [150, 151, 238], although the strength of this association varies between term and preterm gestations [172, 173]. For example, in preterm birth, the frequency of funisitis ranges from 17% to 44.8% [98, 154, 218, 239241], while at term, funisitis is present in only 6.1% to 7.2% and in 1.1% to 4% of cases with and without labor, respectively [157, 160, 235, 237], and its frequency is higher in patients who have rupture of the membranes [157]. …”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrated that term parturition is associated with intra-amniotic infection and/or inflammation [175188]. Patients with acute atherosis were less likely to have placental lesions consistent with amniotic fluid infection.…”
Section: Discussionmentioning
confidence: 99%
“…Acute histologic chorioamnionitis was defined as the presence of acute inflammatory changes characterized by the infiltration of neutrophils in the choriodecidua and amnion [55, 56], respectively; acute funisitis was diagnosed in the presence of neutrophil infiltration into the umbilical vessel walls or Wharton’s jelly, using previously published criteria [5560]. Significant neonatal morbidity was defined as the presence of any of the following conditions: respiratory distress syndrome, bronchopulmonary dysplasia, intraventricular hemorrhage (grade ≥II), periventricular leukomalacia, proven congenital neonatal sepsis, or necrotizing enterocolitis.…”
Section: Methodsmentioning
confidence: 99%